Development of a training environment for training the basics of programming for students of 6-7 grades of general secondary education institutions (Scientific Journal of the Dragomanov Ukrainian State University Series 2 Computer-Oriented Learning Systems, 2020)
The article considers an important section of the training course of computer science – programming. Programming training develops memory, logical thinking, creativity, self-organization, resilience and intellectual abilities. In this case, the number of hours provided by the curriculum in computer science to study the topic "Algorithms and programs", as well as "Fundamentals of object-oriented programming" can be considered more than sufficient (from 30% to 50% depending on the class). Therefore, with a systematic and balanced approach to training, after school-leaving, each student can have a basic knowledge of programming, he will be able to apply it to solve practical problems arising during various activities. At the same time, a variety of development training environments, as well as educational web resources and sites, can help teachers and students. For such modern and simple languages as Python, there are enough of them. However, unfortunately, the available services are not quite suitable for use in grades 6-7 when studying the topic "Algorithms and programs". That is why it is advisable to develop an easy-to-use but meaningful learning environment for training the basics of Python programming in high school. The PyLearn environment is designed to make it easier for students to adapt to the rules of writing code and testing it. Using this approach allow to be devoted to solving practical problems for the maximum part of study time, which in the future, of course, will allow students to deepen their knowledge and to start working on their own educational or research project on programming in the high school.The article is focused on a brief analysis of popular software tools for learning programming, as well as the principle of working with the developed learning environment PyLearn in described.
Keywords: object-oriented programming; programming language; software development environment; training development environment